2002
DOI: 10.1634/theoncologist.7-2004-3
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Role of Topotecan in the Treatment of Recurrent Ovarian Cancer

Abstract: Ovarian cancer is the fifth leading cause of cancer death in women. Most patients with ovarian cancer respond to first-line chemotherapy, but many relapse within 18 to 22 months. The development of efficacious salvage therapies that increase overall survival while maintaining quality of life is a great challenge in the treatment of this disease. Topotecan, a novel topoisomerase I inhibitor, is currently indicated for the treatment of recurrent metastatic carcinoma of the ovary. In patients with relapsed ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…The finding that grade 3 and 4 neutropenia occurred in 69% of the patients corroborates other studies that demonstrated that myelosuppression, particularly neutropenia, is the dose‐limiting toxicity of topotecan (1,2,15,19,20) . We, however, could not find significant differences in toxicity in relation to the number of prior chemotherapy lines.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that grade 3 and 4 neutropenia occurred in 69% of the patients corroborates other studies that demonstrated that myelosuppression, particularly neutropenia, is the dose‐limiting toxicity of topotecan (1,2,15,19,20) . We, however, could not find significant differences in toxicity in relation to the number of prior chemotherapy lines.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that grade 3 and 4 neutropenia occurred in 69% of the patients corroborates other studies that demonstrated that myelosuppression, particularly neutropenia, is the dose-limiting toxicity of topotecan (1,2,15,19,20) . We, however, could not find significant differences in toxicity in relation to the number of prior chemotherapy lines.…”
Section: Discussionsupporting
confidence: 88%
“…In the past 15 years, renewed synthetic interest in 1a and analogues 6 evolved due to findings that substituted derivatives of 1a such as 9-aminocamptothecin (1b), 7 9-((dimethylamino)methyl)-10-hydroxycamptothecin (Topotecan, 1c), 8 and Irinotecan (1d) 9 show low overall toxicity, higher solubility, and still impressive in vivo activity against certain solid tumors. In fact, Topotecan 1c and Irinotecan 1d were recently approved by the FDA for the treatment of ovarian cancer and small-cell lung cancer 10 and refractory colorectal cancer, respectively. 11 Alkaloids structurally related to camptothecin (1a) such as homocamptothecin (2), 12g,13 mappicine (3), 14,15 and mappicine ketone (4) 15 are also of clinical relevance.…”
Section: Introductionmentioning
confidence: 99%